THE ROLE OF FAMILY AND EDUCATIONAL INSTITUTION IN HEALTH PROMOTION AND FORMATION OF CHILDREN’S LIFESTYLE - L. L. Lipanova (Scientific Сentre for Family Health and Human Reproduction Problems, 2013)
Human health potential and regular lifestyle are the things that are fostered during childhood. Family and educational ambience make a significant contribution into the general state of wealth and welfare of our children, the ambience is considered as the main resource of the health and healthy lifestyle creation. A survey was conducted; the goal of the survey was to study the incidence of behavioral risk factors and the role of domestic and school factors in forming of the general education school students' lifestyle. Group of interest: 57 general education schools, 5960 7-11® grade pupils, 912 parents and 240 teachers from Yekaterinburg. Amongst the students the high incidence of behavioral risk factors takes place: disturbed daily regimen (16,6-40,4 % considering certain aspects), low physical activity (70,1 %), alcohol (43,4 %) and tobacco (21,5 %) consumption, insufficient preventive activity. With equally high level of self-assessment of the hygienic knowledge amongst the students of a different age, a lower lifestyle self-assessment and a higher risk factors frequency in regard to the 11th grade pupils' lifestyle were registered. Teenage familiarization with the alcohol and tobacco is associated with a complex of factors characterizing students' personality traits, their school and home life organization. These factors are: low school progress; low motivationfor studying, social life and artistic activity; early labor activity; alcohol and tobacco-friendly family; lack of trust relationship, organization of child's life and behavioral and leisure activities control inside the family. More than half of the schools have certain defects in their health-improving activities, which are often connected with the insufficient level of preventive care-related education of teachers, poor physical training organization of students, lacking clear health promotion assistance policy for students at school, lacking external relations in the area of preventive care. The incidence of behavioral risk factors is associated with such school activity parts as teachers' preventive activity, interaction between school and parents, availability of a school health education system.